PENERAPAN SCRAMBLE DENGAN PICTURE PUZZLE DALAM PENINGKATAN PEMBELAJARAN BAHASA INGGRIS SISWA KELAS IV SDN TUNJUNGSETO TAHUN AJARAN 2015/2016 - Susanti, Resti (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Application of Scramble Model Using Picture Puzzle in Improving English Language Learning Learning for the Fourth Grade Students of Elementary Schools. The objective of this research is to improve English language learning about vocabulary through the application of Scramble with picture puzzle. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection.  Subjects of the research were 24 students of the fourth grade of SDN Tunjungseto. The result of this research is the application of Scramble using puzzle picture can improve English language learning for the fourth grade students of SDN Tunjungseto in the academic year of 2015/2016. It was proven by the increase of percentage of students? learning outcomes in the first cycle 68,60%, in the second cycle 78,85%, and in the third cycle 87,86%. Keywords: Scramble, picture puzzle, English language learning Abstrak: Penerapan Scramble dengan picture puzzle dalam Peningkatan Pembelajaran Bahasa Inggris Siswa Kelas IV SD. Penelitian ini bertujuan untuk meningkatkan pembelajaran bahasa Inggris tentang kosakata melalui penerapan Scramble dengan picture puzzle. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif yang dilaksanakan selama 3 siklus dengan tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas IV SDN Tunjungseto yang berjumlah 24 siswa. Hasil penelitian menunjukkan bahwa penerapan Scramble dengan picture puzzle dapat meningkatkan pembelajaran bahasa Inggris tentang kosakata pada siswa kelas IV SDN Tunjungseto tahun ajaran 2015/2016 yang dibuktikan dengan perolehan persentase rata-rata pada siklus I mencapai 68,60%, pada siklus II meningkat menjadi 78,85%, dan pada siklus III meningkat menjadi 87,86%. Kata kunci: Scramble, picture puzzle, pembelajaran bahasa Inggris